One and one makes three—mothers' and fathers' attachment, mentalizing and parenting sensitivity - Ismair, Selina; Dinzinger, Antonia; Markova, Gabriela; Schropp, Jonas; Brisch, Karl Heinz; Sperl, Wolfgang; Priewasser, Beate (Frontiers in Psychology, 2025)
ObjectiveThis study aims to explore how maternal and paternal attachment representations and their reflective functioning (RF), as operationalization of their mentalizing abilities, influence each other's parental sensitivity within a family systems perspective.BackgroundParental sensitivity is crucial for a child's development, and both parental secure attachment and RF are known to enhance sensitive caregiving. However, the impact of one parent's traits and skills on the other's parenting remains unclear.MethodIn a longitudinal, multi-method study of N = 40 first-time families, including 40 fathers, mothers and their infants each, we assessed parental attachment during pregnancy using the Adult Attachment Interview (AAI). RF was measured twice, as general RF during pregnancy using the RF scale on the AAI, and as parental RF when infants were 6 months using the RF scale on the Parent Development Interview. Additionally, parental sensitivity was observed using the Emotional Availability Scales. To investigate associations between parental measures, we employed an actor-partner interdependence model.ResultsWe found significant associations between attachment representations and general RF in both mothers and fathers, as well as a mediating effect of fathers' parental RF on the relationship between mothers' general RF and paternal sensitivity. Neither fathers' general RF nor parental RF did influence maternal sensitivity.ConclusionThe findings suggest interdependencies between mothers' and fathers' reflective functioning and sensitivity, supporting family systems theory. However, given limitations such as a small, homogeneous sample and lack of causal inference, these results should be interpreted cautiously. Yet, the results may have important implications for practice, in that they suggest that both parent's attachment representations and the ability to mentalize in the triadic system should be considered in family interventions.